Long-Term Use of Ruxolitinib in an AML Patient with Posttransplant Steroid Refractory GVHD - Philip T. Sobash; Achuta K. Guddati; Vamsi Kota (Case Reports in Oncological Medicine)
Ruxolitinib has become a new therapeutic option for steroid refractory graft-versus-host disease (srGVHD), with a substantial remission rate. Its anti-inflammatory properties by blocking interleukin pathways have made it a novel therapeutic approach to inflammatory disease processes, such as GVHD. The long-term use of ruxolitinib has not been explicitly studied outside the context in the treatment of multiple myeloma. With current clinical trials underway for the use of ruxolitinib in srGVHD, there are still no current guidelines or protocols for long-term clinical use. Of the available literature showing ruxolitinib utilization for srGVHD, most cases lead to resolution and eventual discontinuation. We present a case of a 32-year-old male on ruxolitinib with GVHD status postmatched unrelated donor stem cell transplant (MUD SCT) for acute myeloid leukemia (AML) with FLT3 mutation currently on ruxolitinib for 5 years who is not able to tolerate reduction in dosage due to flare-ups. We discuss the clinical implications and nuance of therapy with ruxolitinib with unknown long-term effects and weigh the risks and benefits.